Factors Affecting Climate-Smart Agriculture Practice Adaptation of Farming Households in Coastal Central Vietnam: The Case of Ninh Thuan Province - Duc Truong, Dinh; Tho Dat, Tran; Huy Huan, Le (Frontiers in Sustainable Food Systems, 2022)
Agriculture is a sector with a long tradition and an important contribution to economic growth in Vietnam, providing food security and generating revenue for the country's exports. However, agricultural activities in Vietnam are significantly affected by climate change. In Vietnam, the central coastal area in general and Ninh Thuan province in particular are the most vulnerable areas to natural disasters. In that context, climate-smart agriculture (CSA) is a good strategy to help local famers coping with climate change while securing food security. This study has two main objectives: to assess farmers' awareness on disasters and to analyze factors affecting the decision to apply CSA practices of farming households in Ninh Thuan. The study conducted focus group discussion, in-depth interview and survey of 436 households in 3 districts of Ninh Thuan to collect data. Research results showed that local farmers have a high awareness of natural disasters trends and impacts on agricultural livelihoods. Facing with disasters in the context of climate change, farming households have applied some models of CSA such as minimal tillage, intercropping, crop rotation, crop transformation, and the use of plant varieties. Binary logit regression analysis indicated that age, education level, household income, membership of local associations, training attendance, and support policies were variables significantly influencing the farmers' decision to apply CSA. Challenges for CSA adoption include lack of capital, information, technical support and land ownership institutions in Vietnam. The study also made recommendations to promote CSA in Vietnam, including reforming the legal system, strengthening agricultural extension services, and providing technical and capital support to farmers.